Assessing the potential contribution of excess heat from biogas plants towards decarbonising German residential heating - Jann Weinand; Russell McKenna; Katharina Karner; Lorenz Braun; Carsten Herbes (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2018)
This paper analyses the current technical potential for utilising excess heat from German biogas plants, in order to supply local settlements through district heating. Based on a survey of around 600 biogas plant operators, the fractions of excess heat in these plants are analysed. A heuristic is developed to match biogas plants (heat sources) with local settlements (sinks) in order to determine a least-cost district heating supply for residential buildings. Two criteria are employed, namely the CO2 abatement costs and the payback period, which represent the macro- and microeconomic perspectives respectively. Based on the survey, a mean fraction of 40% excess heat is determined, which is in agreement with other empirical studies. Extrapolating this fraction to the German biogas plant stock leads to technically feasible CO2 savings of around 2.5 MtCO2/a. Employing the criteria of CO2 abatement costs and payback period yields about 2 MtCO2/a below CO2 abatement costs of 200 exteuro/tCO2 and below a payback period of 9 years respectively. This represents about 0.25% of the total German CO2 emissions in 2016 or around 2.5% of all CO2 in residential buildings. If threshold values of 80 exteuro/tCO2 and 5 years are employed, to reflect the German government's suggested external cost of carbon and an expected payback period from an investor's point of view respectively, the carbon reduction potential is about 0.5 MtCO2 and 0.75 MtCO2 respectively. These potentials are concentrated in around 3,500 of 11,400 municipalities, where district heating from biogas plants could reduce CO2 emissions per capita by an average of 250 kgCO_2/a and cover 12% of the total heating demand.
urn:nbn:de:swb:90-863740
Keywords: 330